2019
DOI: 10.1002/slct.201803130
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Conversion of Cellulose into 5‐Hydroxymethylfurfural with CrCl3 Composite Catalyst in Ionic Liquid under Mild Conditions

Abstract: Direct transformation of cellulose (PH101: DP∼200) into 5‐hydroxymethylfurfural (HMF) was investigated using the single CrCl3 or the combination of metal chlorides (CrCl3 with AlCl3, FeCl3, SnCl4, MnCl4, and CuCl2) in ionic liquid [Bmim]Cl under oil‐bath heating. As a result, a novel co‐catalysis CrCl3‐AlCl3 was determined to be the most efficient catalyst for the production of HMF. Compared with single CrCl3, the reaction time with CrCl3‐AlCl3 was reduced by nearly 1/3 when a similar HMF yield (58.3%) was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…It is well known that cellulose hydrolysis conducts readily at the acidic environment, and the conversion of fructose occurred even automatically without catalysts . Nevertheless, direct transformation of cellulose is still a big challenge . In addition, previous studies demonstrated that the isomerization of glucose to fructose has the highest activation energy in cellulose conversion, indicating that this process is the key and rate‐determining step in the consecutive processes of cellulosic biomass valorization.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that cellulose hydrolysis conducts readily at the acidic environment, and the conversion of fructose occurred even automatically without catalysts . Nevertheless, direct transformation of cellulose is still a big challenge . In addition, previous studies demonstrated that the isomerization of glucose to fructose has the highest activation energy in cellulose conversion, indicating that this process is the key and rate‐determining step in the consecutive processes of cellulosic biomass valorization.…”
Section: Methodsmentioning
confidence: 99%
“…Current technologies use an additional isomerization step of glucose to fructose because dehydration of fructose to HMF occurs with better selectivity and higher rates [11,13]. The use of solid catalysts (hydrotalcite, zeolites, and different metal oxides), enzymes, or an aqueous base is renowned in the isomerization step of monosaccharide dehydration [2,6,8,13,14]. However, the high processing cost and the relatively low HMF yields (approximately 20.0-70.0%) are some of the disadvantages in those processes [2,6,8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The use of solid catalysts (hydrotalcite, zeolites, and different metal oxides), enzymes, or an aqueous base is renowned in the isomerization step of monosaccharide dehydration [2,6,8,13,14]. However, the high processing cost and the relatively low HMF yields (approximately 20.0-70.0%) are some of the disadvantages in those processes [2,6,8,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations